New Scarabaeoidea (Coleoptera) from the Lower Cretaceous Yixian Formation, western Liaoning Province, China: Elucidating the systematics of Mesozoic Hybosoridae. (June 2018) - Lu, Yuanyuan; Nie, Ruie; Shih, Chungkun; Ren, Dong; Yang, Xingke; Bai, Ming
Abstract: Two new genera are created to accommodate two new Hybosoridae (Coleoptera: Scarabaeoidea) species: Sinohybosorus cheni gen. et sp. n. and Sinochaetodus tridentatus gen. et sp. n.. The new species are described and illustrated based on two nearly complete fossil specimens from the Lower Cretaceous (Barremian– lower Aptian) Yixian Formation of western Liaoning Province, China. A key of described species of Hybosoridae from the Mesozoic and a catalog of extinct Hybosoridae are provided. Based on the morphological characters, Fortishybosorus ericeusicus Yan, Bai et Ren, 2013 is transferred back to Fortishybosorus instead of Lithohypna in Glaphyridae. The discovery and description of these two new taxa provide further evidence for the Jurassic and Cretaceous diversification of lineages of Hybosoridae. Although the extant Hybosoridae constitute a relative small group in Scarabaeoidea, Hybosoridae are a relatively old group of scarab beetles with relative high diversity in the Mesozoic.